A proteína P21 de Trypanosoma cruzi das cepas G e Y apresenta atividade pleiotrópica na invasão, multiplicação celular, eclosão in vitro e no parasitismo tecidual in vivo - Uombe, Nelsa Paula Inácio (2024)
P21 is a protein secreted by all forms of Trypanosoma cruzi with recognized biological activity. However, the impact of this protein on the cell cycle in this protozoan is still unclear. In our previous studies, we carried out research with the recombinant form of P21, where we demonstrated that it is probably involved in cell invasion and multiplication. Therefore, in order to evaluate the effect of this protein on invasion, multiplication and egress, we generated parasites that do not express (knockout) P21 of the low virulent strain (G strain) and the highly virulent strain (Y strain). Then, we conducted in vitro experiments in Vero and C2C12 cells, infected with tissue culture-derived trypomastigotes (TCT) knockout for P21 (TcP21-/- of strain G and strain Y) and parental parasites of both strains as control (express the Cas9 protein). Also performed in vivo experiments in C57BL/6 INF-/- (knockout for INF) and BALB/c mice infected with TCT G and Y strain, respectively. Invasion and multiplication were performed using the Giemsa staining method, and multiplication was also evaluated by qPCR (24, 48, 72 and 96 hours). Egress was determined by microscopy counting from 72 to 240 hours postinfection. As for in vivo experiments, after the animals were infected, we collected blood from the tail vein every three days until the 15th day post-infection (dpi). After euthanasia, the heart was collected to quantify the parasite DNA by qPCR and for histopathological analysis. In Vero and C2C12 cells, we observed that TcP21-/- strain G parasites invaded significantly less. The 96 hours multiplied significantly less in the Vero cell and similarly in the C2C12 cell. On the other hand, TcP21-/- and parental Y strain parasites invaded and multiplied similarly in Vero cells and invaded significantly less in C2C12 cells. qPCR performed on Vero cells infected with TcP21-/- strain G parasites demonstrated a significantly lower multiplication rate at 24, 48 and 96 hours. And in the C2C12 cell line infected with strain G and Y, we observed a significantly lower amount of T. cruzi DNA in TcP21-/- parasites after 72 hours. The egress of trypomastigotes (strain G) in Vero cells was significantly lower in TcP21-/- parasites compared to controls from 168 hpi and amastigotes was significantly higher at 240 hpi in TcP21-/- parasites. In the C2C12 cell, infected with strain Y, we observed greater egress of TCT and amastigotes in TcP21-/- parasites, but it was significant at 144 hpi in TCT. In vivo, we did not observe patent systemic parasitemia in animals infected with TCT from G strain, as for animals infected with Y strain, we observed patent parasitemia, significantly higher in TcP21-/- parasites from the 3rd to the 6th dpi. The qPCR of heart tissue, in animals infected with G strain, we observed a significantly lower quantity of T. cruzi DNA in TcP21-/- parasites. In Y strain, we observed a significantly higher quantity of DNA in TcP21-/- parasites. The inflammatory response in the heart tissue of animals infected with the G strain was low/medium in TcP21-/- and parental parasites. While in the cardiac tissue infected with Y strain TcP21-/-, we qualitatively observed a higher predominance of neutrophils, macrophages, apoptotic bodies and a large number of amastigote nests. Therewith, we assume that P21 is probably important in the pathogen-host interaction during invasion, cell multiplication and egress. Probably be part of the mechanism that promotes chronic infection without patent systemic parasitemia and acting differently depending on the cell line host and parasite phylogenetic lineage.